INFORMATION SECURITY AS THE BASIS OF INFORMATION ACTIVITY OF THE ARMED FORCES OF UKRAINE - Тична, Богдана Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: the article deals with the research of the content of information security in relation to the information activities of the Armed Forces of Ukraine. Research methods: formal legal and systemic methods are used. Results: based on the analysis of legislation and science-based approaches to understanding the content of information security, existing (and possible) information threats in the country’s defence sphere, the content of information security in the Armed Forces activities is generalized. Based on the analysis of the norms of the Constitution of Ukraine, the principles that determine the information activity of the Armed Forces on information security are formulated. It is defined that information security in the country’s defence sphere is provided by properly adjusted and effective information activities of the Armed Forces in specific areas. Discussion: the dynamic nature of information threats and the search for means and ways of counteracting them in the sphere of activity of the Armed Forces of Ukraine determine the need for further scientific research. It is defined that the main provisions of information activities on ensuring information security are enshrined in the Constitution of Ukraine, the principles of which are detailed in the laws and by-laws of our state adjusting the procedure of creating normal conditions of functioning of military formations, detachments and units, establishing legal regimes of information, including sensitive information, preventing the dissemination of false information in the field of defence of the country, preventing destructive information influence on the personnel of units and population of Ukraine in the sphere of the Armed Forces functioning, cyberattack on departmental and interdepartmental information systems. It is summarized that information security in the Armed Forces activity is focused on the prevention of existing, possible (predicted) threats against the safe functioning of the Armed Forces of Ukraine and their sphere of responsibility and depends directly on the planning, implementation of information activities aimed at preventing the implementation of information threats into reality and clearly respecting the legislation during the implementation of certain types of information activities of the Armed Forces of Ukraine.